Office XP Bible - Willett, Edward C. (New York : Hungry Mind, Inc, 2001)
The Office XP Bible by Edward C. Willett and Steve Cummings is a comprehensive 1,392-page guide published in 2001, designed to assist users in mastering Microsoft Office XP applications. The book covers essential tools such as Word, Excel, Access, Outlook, PowerPoint, Publisher, and FrontPage, providing detailed instructions, tips, and techniques to enhance productivity and proficiency.